Β2-Adrenoceptors inhibit neutrophil extracellular traps in human polymorphonuclear leukocytes. Issue 3 (18th April 2018) - Marino, Franca; Scanzano, Angela; Pulze, Laura; Pinoli, Monica; Rasini, Emanuela; Luini, Alessandra; Bombelli, Raffaella; Legnaro, Massimiliano; de Eguileor, Magda; Cosentino, Marco
Abstract: This study tests the hypothesis that in isolated human polymorphonuclear leukocytes (PMN) adrenergic ligands can affect neutrophil extracellular trap (NET) formation. We have previously shown that, in PMN, adrenaline (A), through the activation of adrenergic receptors (AR), reduces stimulus-dependent cell activation; we have, therefore, planned to investigate if AR are involved in NET production. PMN were obtained from venous blood of healthy subject. The ability of adrenergic ligands to affect reactive oxygen species (ROS) production, NET production, and cell migration was investigated in cells cultured under resting conditions or after activation with N -formyl-methionyl-leucyl-phenylalanine (fMLP), LPS, or IL-8. Stimuli-induced NET production measured as ROS, microscopic evaluation, and elastase production was reverted by A and this effect was blocked by the selective β2 –AR antagonist ICI-118, 551. The stimulus-induced ROS generation and migration was prevented by A and by isoprenaline (ISO), and these effects were counteracted only by ICI-118, 551 and not by the other two selective ligands for the β1 and β3 –AR. Finally, the presence of the β–ARs on PMN was confirmed, by means of microscopy and flow cytometry. The data of the present study suggest that adrenergic compounds, through the interaction of mainly β2 –AR, are able to affect neutrophil functions. These data are suggestive of a possible therapeutic role of β2 –AR ligands (in addition to their classical use), promoting the possible therapeutic relevance of adrenergic system in the modulation of innate immunity proposing their possible use as anti-inflammatory drugs. Adrenergic compounds modify NET production by human neutrophils and are able to affect other key functions of these cells.